2014
DOI: 10.1007/s00464-014-3819-9
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic robot-assisted versus open total pancreatectomy: a case-matched study

Abstract: LRATP is feasible in selected patients, but further experience is needed to draw final conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 45 publications
0
35
2
4
Order By: Relevance
“…Recent studies have shown that laparoscopic robot-assisted pancreaticoduodenectomy (RAPD) may be safely feasible [1,2,3,4,5,6,7,8,9,10]. The da Vinci surgical system (dVss; Intuitive Surgical Inc., Sunnyvale, Calif., USA) is a computer-assisted telemanipulator, which allows a remote surgeon to handle tissues, drive electromechanical devices and perform intracorporeal sutures while working through laparoscopic ports.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that laparoscopic robot-assisted pancreaticoduodenectomy (RAPD) may be safely feasible [1,2,3,4,5,6,7,8,9,10]. The da Vinci surgical system (dVss; Intuitive Surgical Inc., Sunnyvale, Calif., USA) is a computer-assisted telemanipulator, which allows a remote surgeon to handle tissues, drive electromechanical devices and perform intracorporeal sutures while working through laparoscopic ports.…”
Section: Introductionmentioning
confidence: 99%
“…TP combines the operative steps of distal pancreatectomy and pancreaticoduodenectomy, but it lowers the risk of pancreatic stump‐related morbidity. Initial reports of TP via minimally invasive approaches have been encouraging, although they have been performed in select patients .…”
Section: Discussionmentioning
confidence: 99%
“…Mortality and morbidity rates of robotic PD have been shown to be similar to laparoscopic and open surgical techniques with decreased mean blood loss compared to open surgery (35,36). To sum up, although it has not been clearly shown whether RAL hepatic and pancreatic surgery are superior to the laparoscopic technique in selected patients, authors report that the robotic technique can be performed safely in hepatic and pancreatic surgery.…”
Section: Robotic Hepatopancreaticobiliary System Surgerymentioning
confidence: 97%